Human identity and bioethics - DeGrazia, David (Cambridge University, 2013)
When philosophers address personal identity, they usually explore numerical identity. When nonphilosophers address personal identity, they often have in mind narrative identity. This book develops accounts of both senses of identity, arguing that both are normatively important, and is unique in its exploration of a wide range of issues in bioethics through the lens of identity. Defending a biological view of our numerical identity and a framework for understanding narrative identity, David DeGrazia investigates various issues for which considerations of identity prove critical.